(untitled) (AYUSHDHARA, 2019)
According to fundamentals of Ayurveda Agni has an important role in the physiological functioning of body. Agni is broadly described in three types Jatharagni, Bhutagni, Dhatvagni. The Jatharagni is Param– Sukshma and a unit which transforms of Aahara (food substances) into various forms which can be easily assimilated by our body. When it is in good quality it covert ingested food into absorbable form which gives energy to each and every tissue of the body. Therefore all components present in own body are depending upon Agni directly or indirectly. It helps in the balance condition of the three Doshas or humors namely Vata, Pitta, Kapha. As in classics of Ayurveda all diseases are caused due to Mandagni (hampered function of Agni) -“Roga Sarvepi Mandagnou”. If Agni becomes hampers, it will result into improper formation of Rasadhatu and consequently Uttorotar Dhatu formation hampers. Once the Srotus becomes abnormal, it brings abnormality in normal Dhatu by not transporting to required destination, so Srotus vitiates other Srotus and Dhatu, Dhatu vitiates other Dhatu, and for all these imbalanced Dosha are responsible. Agnidushti (Improper functioning of Agni) causes imbalance in the level of Tridosha which results in pathogenesis of various disease. That’s why Agnidushti play an important role in pathogenesis of various diseases.